Ivabradine Improves Heart Rate Variability in Patients with Nonischemic Dilated Cardiomyopathy - Kurtoglu,Ertugrul (2014)
Background: Ivabradine is a novel specific heart rate (HR)-lowering agent that improves event-free survival in patients with heart failure (HF). Objectives: We aimed to evaluate the effect of ivabradine on time domain indices of heart rate variability (HRV) in patients with HF. Methods: Forty-eight patients with compensated HF of nonischemic origin were included. Ivabradine treatment was initiated according to the latest HF guidelines. For HRV analysis, 24-h Holter recording was obtained from each patient before and after 8 weeks of treatment with ivabradine. Results: The mean RR interval, standard deviation of all normal to normal RR intervals (SDNN), the standard deviation of 5-min mean RR intervals (SDANN), the mean of the standard deviation of all normal-to-normal RR intervals for all 5-min segments (SDNN index), the percentage of successive normal RR intervals exceeding 50 ms (pNN50), and the square root of the mean of the squares of the differences between successive normal to normal RR intervals (RMSSD) were low at baseline before treatment with ivabradine. After 8 weeks of treatment with ivabradine, the mean HR (83.6 ± 8.0 and 64.6 ± 5.8, p < 0.0001), mean RR interval (713 ± 74 and 943 ± 101 ms, p < 0.0001), SDNN (56.2 ± 15.7 and 87.9 ± 19.4 ms, p < 0.0001), SDANN (49.5 ± 14.7 and 76.4 ± 19.5 ms, p < 0.0001), SDNN index (24.7 ± 8.8 and 38.3 ± 13.1 ms, p < 0.0001), pNN50 (2.4 ± 1.6 and 3.2 ± 2.2 %, p < 0.0001), and RMSSD (13.5 ± 4.6 and 17.8 ± 5.4 ms, p < 0.0001) substantially improved, which sustained during both when awake and while asleep. Conclusion: Our findings suggest that treatment with ivabradine improves HRV in nonischemic patients with HF.